Responding to the biodiversity impacts of a megafire: A case study from south‐eastern Australia's Black Summer. (6th May 2021) - Geary, William L.; Buchan, Anne; Allen, Teigan; Attard, David; Bruce, Matthew J.; Collins, Luke; Ecker, Tiarne E.; Fairman, Thomas A.; Hollings, Tracey; Loeffler, Ella; Muscatello, Angela; Parkes, David; et al.
Abstract: Aim: Megafires are increasing in intensity and frequency globally. The impacts of megafires on biodiversity can be severe, so conservation managers must be able to respond rapidly to quantify their impacts, initiate recovery efforts and consider conservation options within and beyond the burned extent. We outline a framework that can be used to guide conservation responses to megafires, using the 1.5 million hectare 2019/2020 megafires in Victoria, Australia, as a case study. Location: Victoria, Australia. Methods: Our framework uses a suite of decision support tools, including species attribute databases, ~4, 200 species distribution models and a spatially explicit conservation action planning tool to quantify the potential effects of megafires on biodiversity, and identify species‐specific and landscape‐scale conservation actions that can assist recovery. Results: Our approach identified 346 species in Victoria that had >40% of their modelled habitat affected by the megafire, including 45 threatened species, and 102 species with >40% of their modelled habitat affected by high severity fire. We then identified 21 candidate recovery actions that are expected to assist the recovery of biodiversity. For relevant landscape‐scale actions, we identified locations within and adjacent to the megafire extent that are expected to deliver cost‐effective conservation gains. Main conclusion: The 2019/2020 megafires in south‐eastern Australia affected the habitat of many species and plant communities. Our framework identified a range of single‐species (e.g., supplementary feeding, translocation) and landscape‐scale actions (e.g., protection of refuges, invasive species management) that can help biodiversity recover from megafires. Conservation managers will be increasingly required to rapidly identify conservation actions that can help species recover from megafires, especially under a changing climate. Our approach brings together commonly used datasets (e.g., species distribution maps, trait databases, fire severity mapping) to help guide conservation responses and can be used to help biodiversity recover from future megafires across the world.